Attenuation of Listeria monocytogenes Virulence by Cannabis sativa L. Essential Oil - Marini, Emanuela; Magi, Gloria; Ferretti, Gianna; Bacchetti, Tiziana; Giuliani, Angelica; Pugnaloni, Armanda; Rippo, Maria Rita; Facinelli, Bruna (Frontiers in Cellular and Infection Microbiology, 2018)
Anti-virulence strategies are being explored as a novel approach to combat pathogens. Such strategies include inhibition of surface adhesion, tissue invasion, toxin production, and/or interference with the gene regulation of other virulence traits. Listeria monocytogenes, the causative agent of listeriosis, is a facultative intracellular food pathogen characterized by a wide distribution in the environment. Its ability to persist within biofilms and to develop resistance to sanitizers is the cause of significant problems in food processing plants and of steep costs for the food industry. In humans, the treatment of listeriosis is hampered by the intracellular location of listeriae and the poor intracellular penetration of some antibiotics. Eleven L. monocytogenes isolates from patients who were diagnosed with invasive listeriosis in Italy in 2014–2016 were studied. This in vitro and in vivo study explored the antibacterial and anti-virulence properties of a steam-distilled essential oil of Cannabis sativa L., which is being intensively investigated for its high content in powerful bioactive phytochemicals. Susceptibility experiments demonstrated a moderate bactericidal activity of the essential oil (Minimum Bactericidal Concentration > 2048 μg/mL). Assessment of the effects of sublethal concentrations of the essential oil on L. monocytogenes virulence traits demonstrated a significant action on motility. Listeriae were non-motile after exposure to the essential oil. Light and scanning electron microscopy documented aggregates of listeriae with the flagella trapped inside the cluster. Real-time RT-PCR experiments showed downregulation of flagellar motility genes and of the regulatory gene prfA. The ability to form biofilm and to invade Caco-2 cells was also significantly reduced. Galleria mellonella larvae infected with L. monocytogenes grown in presence of sublethal concentrations of the essential oil showed much higher survival rates compared with controls, suggesting that the extract inhibited tissue invasion. Food contamination with L. monocytogenes is a major concern for the food industry, particularly for plants making ready-to-eat and processed food. The present work provides a baseline in the study of the anti-virulence properties of the C. sativa essential oil against L. monocytogenes. Further studies are needed to understand if it could be used as an alternative agent for the control of L. monocytogenes in food processing plants.